Behavioural Change according to the Si/Al Ratio of Successive Na-Mordenites Observed through Their Dielectric Relaxation during Water Vapour Adsorption Process. (3rd February 2016) - Diaby, Sekou
Abstract : The experimental study of water vapour adsorption phenomenon on a zeolite, by dielectric relaxation measurement, makes it possible to determine the variations in the exchangeable cation hopping activation energy, on the surface of the solid, in relation to the number of adsorbed molecules. The present work shows that it is possible to explain the change observed in the energy, by means of simple assumptions based, on the one hand, on the models used in order to simulate the adsorption process and, on the other hand, on the distribution of the molecules adsorbed near the exchangeable cations. Thus, the phenomenological interpretation suggested here, about the change in the exchangeable cation hopping energy, obtained by dielectric relaxation measurement, makes us with a mind to conceive a simple method for explaining the results leading to new information on the organization of the first adsorbed molecules on the surface of the studied zeolite. Then, it can be verified that these conclusions confirm the assumptions already developed for interpreting the inferences from previous experiments carried out by means of other techniques.